Examining Sentence Comprehension Deficit and its Relationship With Production Measures of Mean Length of Utterance and Mean Length of Sentence in Persian-speaking Adults with Agrammatism - Samaneh Sazegar Nejad; Fariba Yadegari; Robab Teymouri; Enayatollah Bakhshi (Journal of Rehabilitation, 2025)
Objective This study examines differences in the comprehension of canonical and non-canonical sentences in Persian speakers with agrammatism. Additionally, it examines the relationship between sentence comprehension and the production measures of mean utterance length and mean sentence length to determine whether shared syntactic representations serve as the basis for both comprehension and production deficits in agrammatism. Materials & Methods 21 individuals with non-fluent aphasia and agrammatism (9 women, 12 men; mean age: 54.23 years) participated in this descriptive-analytical study. To establish normative criteria, 21 non-brain-damaged individuals, matched with the aphasic group in gender, age, and education, served as the control group. Sentence comprehension was assessed using the bilingual aphasia test, including the overall sentence comprehension score and scores for canonical and non-canonical sentences. Mean utterance length and mean sentence length were evaluated through descriptive, narrative, and story-retelling discourse across eight tasks. Between-group comparisons included differences in sentence comprehension, comprehension of canonical and non-canonical sentences, and production measures of mean length of utterance (MLU) and mean sentence length. Since the control group achieved perfect scores, within-group comparisons were conducted only in the agrammatic group to examine differences in processing canonical versus non-canonical sentences. Finally, the relationship between sentence comprehension and production measures was analyzed in the agrammatic group. Results Between-group comparisons showed that the agrammatic group scored significantly lower in the syntactic comprehension test (P<0.05), comprehension of canonical sentences (P<0.05), comprehension of non-canonical sentences (P<0.05), MLU (P<0.05), and mean sentence length (P<0.05). Within-group comparisons in the agrammatic group indicated significant differences in comprehending canonical and non-canonical sentences (P<0.05). Among non-canonical structures, object-cleft and object-topicalized sentences were significantly more challenging than subject-cleft and subject-topicalized sentences (P<0.05). Additionally, MLU and mean sentence length showed a significant correlation with syntactic comprehension (P<0.05). Conclusion The findings revealed that sentence comprehension skills in individuals with agrammatism are significantly lower than those of their non-brain-damaged counterparts. Additionally, Persian speakers with agrammatism experience considerable difficulty processing non-canonical structures with derived word order, such as object-topicalized and object-cleft sentences. Furthermore, production measures of mean utterance and sentence length were significantly correlated with sentence comprehension. These findings emphasize the importance of syntactic complexity and word order variations in sentence processing in individuals with agrammatism and can contribute to the development of effective language rehabilitation strategies.